South American tomato moth (Tuta absoluta) and tomato protection measures in the conditions of the Northern Steppe of Ukraine - F. S. Melnychuk; S. A. Alekseeva; O. V. Hordiienko; I. M. Ostryk; A. V. Antonyuk (Меліорація і водне господарство, 2021)
Cultivation of nightshade family crops (Solanaceae) requires sufficient amount of moisture and heat. In Ukraine, the most available conditions for that are in the southern regions: Kherson, Mykolaiv, Odesa, Zaporizhia and AR of Crimea, where the average yield of tomatoes is about 30 t/ha, and planting area is about 470 thousand hectares. Tomatoes are the main host plants for the South American tomato moth. Leaves, fruits and vegetative buds damaged by these pests, become a kind of «gateway» for the infection of plants by fungal pathogens. Feeding of phytophagous on the fruits of tomato leads to their falling off. Yield losses can reach 100%. This pest has high adaptability to climatic and natural conditions, capable for reproductive activities throughout the year. Among the factors contributing to the spread of these pests at the intercontinental level, the most important is the uncontrolled trading of infected fruits with plant particles, and the local spread from one field to another due to the ability of adult moths to fly. The searching of scientifically grounded methods of control of South American tomato moth, in particular, the study of the effectiveness of modern insecticides by means of spraying and drip application along with applying irrigation against this pest in the Steppe of Ukraine is very actual.